Hydronephrosis after radical hysterectomy: A prospective study - Prapaporn Suprasert (2018)
One part of the operative procedure of radical hysterectomy (RH) is the dissection of the ureter from its overlying tissue and this may result in injury to the ureteric adventitia. This might induce ureteric obstruction and consequently produce hydronephrosis. The objective of this prospective study was to evaluate the incidence of hydronephrosis after RH in patients with early stage cervical cancer. From July 2006 through March 2007, 77 patients with IA2-IIA cervical cancer who planned to undergo radical hysterectomy and pelvic lymphadenectomy (RHPL) received urinary tract ultrasonography 5 times (one day before surgery and 7 days, 6 weeks, 3 months and 6 months after the operation) from one radiologist. Patients who had hydronephrosis before surgery, suffered intraoperative ureteric injury, or were lost follow-up at 7 days after surgery were excluded from the study. Urinary tract ultrasonography was performed on 77, 55, 52 and 52 patients at each visit. Right hydronephrosis was detected in 16, 7, 5 and 3 patients, and left hydronephrosis in 16, 11, 3 and 1, at 7 days, 6 weeks, 3 months and 6 months, respectively, after the operation. Hydronephrosis persisted in 8 patients (15%) after 3 months. Two of these had undergone exploratory laparotomy for lysis of ureteral adhesions. One patient who developed hydronephrosis had local recurrence and received further treatment with concurrent chemoradiation therapy. In conclusion, the incidence of persistent hydronephrosis over 3 months after RHPL was 15%, even without intra-operative ureteric injury. However, only a few cases required surgical intervention.